The potential of mobile augmented reality as a didactic and pedagogical source in learning geometry 3D - Poppy Yaniawati; Sudirman Sudirman; Mellawaty Mellawaty; Rully Indrawan; Melinda Putri Mubarika (OmniaScience, 2023)
The COVID-19 pandemic in Indonesia requires teachers and students to perform learning activities online. Meanwhile, teachers use a variety of technology products in the classroom without paying attention to the didactic, pedagogical, and content aspects. This is due to time constraints and short learning adjustments that should be flexible to this pandemic. Therefore, this research provides an alternative by exploring the potential of augmented reality as a didactic and pedagogical source in learning geometry. An exploratory case study design was used to reveal this potential, while three mathematics teachers and twenty-six students from three schools in Indramayu Regency, Indonesia, participated in the research. Data from observations and documentation were checked, extracted, entered verbatim, and coded. The results of the interview data were analyzed using the content analysis method, while those from the geometry understanding test and student response questionnaires used descriptive analysis. Consequently, the research results showed that augmented reality was useful as an alternative didactic and pedagogical source of learning geometry during the COVID-19 pandemic. This conclusion was based on the reason, first characteristically augmented reality technology can be integrated with textbooks or certain learning methods. Second, the results of the geometry understanding test showed that there were more students who answered the questions correctly than the students who answered incorrectly. Third, the results of questionnaires and interviews showed that students had a positive attitude during the geometry learning process. Therefore, the researcher believes that the use of augmented reality is worthy of being an alternative didactic and pedagogical source and has the potential to be applied to other subjects both during the COVID-19 pandemic and after the COVID-19 pandemic.